Integrative taxonomy versus taxonomic authority without peer review: the case of the Oriental fruit fly, Bactrocera dorsalis(Tephritidae) - Schutze, Mark K.; Bourtzis, Kostas; Cameron, Stephen L.; Clarke, Anthony R.; Meyer, Marc De; Hee, Alvin Kah Wei; Hendrichs, Jorge; Krosch, Matthew N.; Mwatawala, Maulid (Wiley-Blackwell Publishing, 2017)
1. Major global horticultural and food security tephritid fruit fly pests,Bactrocera papayae(papaya fruit fly) andB. invadens(invasive fruit fly), weresynonymised withB. dorsalis(Oriental fruit fly) by Schutzeet al.(2015a) based onextensive integrative taxonomic evidence from multiple sources. This synonymy waspeer reviewed by eight independent experts.2. Drew & Romig (2016) withdrewB.papayaeandB.invadensfrom synonymy based onopinion drawn primarily from disparate geographical distribution, morphological, andhost use information. This reversal was not subjected to peer review.3. We consider the withdrawal from synonymy as invalid due to significant errors andmisrepresentations of the literature provided in the arguments of Drew & Romig (2016)that we propose would not have withstood peer scrutiny.4. This case reflects a broader issue of individual taxonomic authorities using opinionto challenge extensive evidence generated via scientific hypothesis-testing methods bydiscipline specialists.5. We recommend that taxonomic acts not subjected to peer review, especially of pestspecies, be actively discouraged by the broader scientific and regulatory community.